Cryptococcosis by Cryptococcus neoformans/Cryptococcus gattii Species Complexes in non-HIV-Infected Patients in Southeastern Brazil - Erika Nascimento; Patrícia Helena Grizante Barião; Marcia Regina von Zeska Kress; Fernando Crivelenti Vilar; Rodrigo de Carvalho Santana; Gilberto Gambero Gaspar; Roberto Martinez (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTION: The clinical manifestations of cryptococcosis are usually associated with the infecting agents Cryptococcus neoformans (CN) and C. gattii (CG) species complexes and the host. In this study, non-HIV-infected patients, at a university hospital in southeastern Brazil, had epidemiological and clinical data associated with cryptococcal disease and isolated Cryptococcus species: CN - 24 patients and CG - 12 patients. METHODS: The comparison was comprised of demographic data, predisposing factors, clinical and laboratory manifestations, and outcomes of cryptococcosis patients treated between 2000 and 2016. Immunocompetent and immunosuppressed patients were also compared, irrespective of the infecting species. Cryptococcus spp. were genotyped by PCR-RFLP analysis of the URA5 gene. RESULTS: Infections by the CN species complex (100% VNI genotype) were associated with drug immunosuppression and fungemia, and patients infected with the CG species complex (83% VG II and 17% VGI genotypes) had more evident environmental exposure and higher humoral response. CN and CG affected patients with or without comorbidities. CONCLUSIONS: Diabetes mellitus, other chronic non-infectious diseases, and alcoholism were likely predisposing factors for infection by both CN and CG species. Immunocompetent patients, independent of the infecting Cryptococcus species complexes, showed a higher occurrence of meningitis and a trend toward less fungal dissemination and longer survival than immunosuppressed hosts.